PROFESSOR DR. SYED AZHAR RECEIVES INTERNATIONAL AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SM, PENANG, 8 March 2016 – Professor Dr. Syed Azhar Syed Sulaiman, who lectures at the School of Pharmaceutical Sciences, Universiti Sains Malaysia (USM) has been acknowledged for his expertise in the field of Clinical Pharmacy, in conjunction with the 50 Years Golden Jubilee celebration of the Pharmacy Faculty at the University of Khartoum in Sudan recently.